Anomalously Faster Deterioration of LiNi0.8Co0.15Al0.05O2/Graphite High-Energy 18650 Cells at 1.5 C than 2.0 C. (31st July 2018) - Cui, Dawei; Wang, Jinlong; Sun, Ailing; Song, Hongmei; Wei, Wenqing
Abstract : Discharge rate is a key parameter affecting the cycle life of lithium-ion batteries (LIB). Normally, lithium-ion batteries deteriorate more severely at a higher discharge rate. In this paper, we report that the cycle performance of LiNi0.8 Co0.15 Al0.05 O2 /graphite high-energy 2.8 Ah 18650 cells is abnormally worse at a 1.5 C discharge rate than at a 2.0 C discharge rate. Combining macromethods with micromethods, the capacity/rate performance, electrochemical impedance spectroscopy (EIS), and scanning electron microscope (SEM) morphology of the electrodes are systematically investigated. We have found that the impedance of the negative electrodes after 2.0 C aged is smaller than that after 1.5 C aged, through EIS analysis, and the discharge rate performance of the negative electrodes after 2.0 C aged is better than that after 1.5 C aged through coin cell analysis. In addition, some special microcracks in the negative electrodes of aged cells are observed through SEM analysis, which can accelerate the side reaction between active and electrolyte and form the thicker SEI which will hinder the Li + insertion and cause resistance increase. In short, the LiNi0.8 Co0.15 Al0.05 O2 /graphite-based lithium-ion batteries show better cycle life at a 2.0 C discharge rate than at a 1.5 C discharge rate which indicates that the negative electrodes contribute more than the positive electrodes.